Plant-based bioactives and oxidative stress in reproduction: anti-inflammatory and metabolic protection mechanisms - Liu, Xue; Zeng, Tongtong; Zhang, Enfeng; Bin, Chengli; Liu, Qun; Wu, Kun; Luo, Yiping; Wei, Shaobin (Frontiers in Nutrition, 2025)
Oxidative stress plays a central role in reproductive disorders, with food bioactive compounds offering therapeutic potential through their antioxidant properties. This review examines antioxidant active ingredients from plant-based foods and their protective mechanisms in reproductive system oxidative stress management. Key phytochemicals including polyphenols (flavonoids, phenolic acids such as curcumin, resveratrol, and EGCG), carotenoids (lycopene, lutein), and organosulfur compounds demonstrate potent free radical scavenging capacity, regulate antioxidant enzyme activity, and inhibit lipid peroxidation through Nrf2 pathway activation and NF-κB inhibition. These natural food ingredients provide anti-inflammatory effects and metabolic benefits including improved insulin sensitivity and mitochondrial protection. Clinical evidence shows lycopene supplementation (4–8 mg/day) improves sperm motility and reduces DNA fragmentation in male infertility, resveratrol (150 mg/day) enhances ovarian reserve markers in female fertility, and curcumin reduces inflammatory markers (IL-8, TNF-α) in endometriosis while improving assisted reproductive outcomes. However, poor bioavailability limits therapeutic efficacy, with most compounds showing < 10% absorption. Advanced delivery technologies, including nanoencapsulation (5–30 fold enhancement), phospholipid complexation, and formulation with absorption enhancers (e.g., piperine), can substantially improve the bioavailability of these compounds for functional foods and dietary supplements. Emerging single-cell and multi-omics approaches provide powerful tools to unravel tissue-specific mechanisms, while future progress also depends on establishing uniform dosage standards and conducting rigorous safety assessments to address potential pro-oxidant effects and long-term interactions. Given that infertility affects 17.5% of adults globally, food-derived antioxidant interventions represent accessible strategies for managing reproductive disorders, supporting the development of nutraceuticals and novel foods for reproductive health protection.